Effectiveness of dental and oral health counseling using traditional folklore video media on knowledge in 8-9-year-old children - Pratama, I Wayan Gita; Widiati, Sri; Priyono, Bambang; Santoso, Aloysia Supartinah; Handajani, Juni; Hanindriyo, Lisdrianto (Majalah Kedokteran Gigi Indonesia, 2024)
Oral health problems among elementary school children are still very common. One of the contributing factors is behavior in maintaining oral hygiene. Behavior is established from knowledge which will then stimulate changes in attitudes and practice. Efforts to enhance knowledge in children can be achieved through counseling. This study aimed to determine the effectiveness of oral health counseling using traditional folklore video media on knowledge in children aged 8-9 years. This was quasi-experimental research with a two group pre-test and post-test design. Sampling was conducted using multistage cluster random sampling with a total sample of 112 children aged 8-9 years in elementary schools. The sample was divided into 2 groups: 56 children using traditional folklore video as the intervention group and 56 children using conventional video as the control group. Knowledge variables were measured using a questionnaire; most of the data were not normally distributed so data analysis was carried out using the Mann-Whitney U Test. The results of the difference analysis using the Mann-Whitney U Test at pre-post 2 showed a significant increase in knowledge in both groups. The median knowledge score of the traditional folklore video group showed a greater increase compared to the conventional video group by 13 (6.6 - 20) (p < 0.001). This study concluded that oral health counseling using traditional folklore video is more effective in increasing oral health knowledge in children aged 8-9 years compared to conventional video media.